International economics and policy an introduction to globalization and inequality - Maskus, Keith E. (Keith Eugene) (World scientific lecture notes in economics and policy, 2024)
Relying on economic theory where necessary, this book emphasizes translating that theory into practical applications that will help students appreciate the clear importance of understanding how countries, businesses, workers, and governments interact with each other. It offers in-depth analysis, empirical evidence, and practical examples arising from all the forms of international exchange: international trade, or the exchange of goods and services across borders; international finance, or the roles that currencies, exchange rates, prices, and monetary systems play in facilitating global investment and trade; global migration, through which workers move from lower-wage countries to higher-wage countries; the international flows of capital and knowledge through multinational enterprises and global supply chains; and the global policy architecture underlying these flows"--